Early childhood allergy linked with development of attention deficit hyperactivity disorder and autism spectrum disorder. Issue 6 (17th June 2022) - Nemet, Shay; Asher, Ilan; Yoles, Israel; Baevsky, Tuvia; Sthoeger, Zev
Abstract: Background: Previous studies reported controversial results regarding the association between allergic disorders and attention deficit hyperactivity disorder (ADHD)/autism spectrum disorder (ASD). The aim of this article was to investigate whether allergic disorders are associated with ADHD/ASD in a large cohort of pediatric patients. Methods: A retrospective study using the pediatric (0–18 year) database (ICD‐9‐CM codes) of Clalit Health Services during the years (2000–2018). Diagnosis of all disorders was made by specialist physicians. Results: A total of 117 022 consecutive non‐selective allergic children diagnosed with one or more allergic disorder (asthma, rhinitis, conjunctivitis, skin, food, or drug allergy) and 116 968 non‐allergic children were enrolled to our study. The mean follow‐up period was 11 ± 6 years. The presence of allergic disorders in early childhood (mean age of allergic diagnosis 4.5 ± 4.3 years) in boys as well as in girls significantly increased the risk to develop ADHD (O.R 2.45, CI 2.39–2.51; p < .0001), ASD (O.R 1.17, CI 1.08–1.27; p < .0001), or both ADHD + ASD (O.R 1.5, CI 1.35–1.79; p < .0001). Children with more than one allergic comorbidity revealed a much higher risk. In a multivariable analysis (adjusted for age at study entry, number of yearly visits, and gender), the risk of allergic children to develop ADHD and ADHD + ASD, but not ASD alone, remained significantly higher. Conclusion: Allergic disorder in early childhood significantly increased the risk to develop ADHD, and to a less extend ASD, in later life.